Passive Smoke: The EPA's Betrayal of Science and Policy - Pérusse, Michel (Relations industrielles / Industrial Relations, 1999)
The article reviews the book, "Passive Smoke: The EPA's Betrayal of Science and Policy," by Gio B. Gori and John C. Luik.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Cancer; Causes; Labor Unions; Laws & regulations; Smoking in the workplace; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Perdre sa vie à la gagner ; manuel pour la santé des travailleurs - Boulard, René; Pérusse, Michel (Relations Industrielles / Industrial Relations, 1981)
This article reviews the book, "Perdre sa vie à la gagner ; manuel pour la santé des travailleurs," by Jeanne M. Stellman & Susan M. Daum.